Inhibition of the E2F-1/p53/Bax pathway by tauroursodeoxycholic acid in amyloid beta-peptide-induced apoptosis of PC12 Cells - Ramalho, RM (2015)
Amyloid beta-peptide (Abeta)-induced cell death may involve activation of the E2F-1 transcription factor and other cell cycle-related proteins. In previous studies, we have shown that tauroursodeoxycholic acid (TUDCA), an endogenous bile acid, modulates A